The Influence Of Community Participation And Policy Implementation On Equitable Welfare In Bogor District Through The Samisade Program - Triana Pertiwi; Harianto, Harianto; Lala M. Kolopaking (SEAN Institute, 2024)
The aim of decentralization is to increase the empowerment of independently owned potential in an effort to improve the welfare of the people in their respective regions. But real conditions do not describe the ideal situation that is expected. Economic development is not accompanied by equal distribution of income and disparities still exist. Bogor Regency has an average Gini Ratio value of 0.4 in 2018-2020, indicating that inequality is approaching a critical point and has the potential to give rise to social jealousy. Equal distribution of community welfare has become a strategic issue in the 2018-2023 Bogor Regency RPJMD which is manifested in financial assistance for village infrastructure for the Samisade program (Samilyar Sadesa – One Billion One Village) with the concept of developing villages. The community can actively participate in preparing and implementing priority programs that have been formulated together and have the same rights in receiving this assistance. Therefore, a study is needed regarding the contribution of community participation and policy implementation to the effectiveness of the Samisade Program as well as the contribution of community participation and policy implementation through the Samisade Program to equal distribution of welfare through the program. The research method used was descriptive quantitative based on data obtained through questionnaires distributed to 100 villages in 12 sub-districts. Data analysis using SmartPLS.